Perbandingan Pola Pengasuhan di Pesantren Provinsi Sulawesi Selatan dan Provinsi Daerah Istimewa Yogyakarta - Syamsudduha, St.; T, M. Yusuf (Al Asma: Journal of Islamic Education, 2025)
Islamic boarding school is one of the religious-based educational institutions that has an important role in shaping the character and personality of students. The parenting pattern applied in pesantren is one of the main factors that influence the development of students, both academically and morally. Each pesantren has different characteristics and approaches to parenting, depending on its values, traditions, and facilities and infrastructure. This study aims to compare parenting patterns in Pesantren DDI Mangkoso, South Sulawesi, which represents traditional pesantren, and Pesantren Muallimat Yogyakarta, DI Yogyakarta, which represents modern pesantren. The research used an ex post facto quantitative method with a survey approach. The research sample was determined through multistage random sampling technique, and data were collected using questionnaires, observations, and interviews. Data were analyzed descriptively and inferentially with a t-test at the 5% significance level. The results showed that the implementation of parenting was significantly different in the aspects of communication, emotion management, use of free time, monitoring students' activities, problem solving, and discipline in complying with dormitory rules. However, in the aspects of monitoring activities and enforcing discipline for students, the differences are not significant. The differences in the implementation of parenting in the two research locations are mainly due to differences in the organization and means of supporting parenting. This study provides an in-depth description of the factors that influence parenting patterns in traditional and modern pesantren, which can be the basis for developing parenting policies based on pesantren values and culture.